2018
DOI: 10.1007/s12020-018-1676-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism: findings from the retrospective evaluation of cases over a 6-year period from a regional UK centre

Abstract: PTX treatment is associated with cure of disease in patients with PHPT with acceptable risk of complications. Improvements in diagnostic work-up and follow-up care should improve the morbidity from PHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…We describe a large series of patients with pHPT and their clinical evolution over time. Consistent with other series [17,26], we have obtained high cure (99%) and low recurrence (4.3%) rates. This study shows recurrences occurred with a median of 6.5 years after parathyroidectomy, whereas other studies have reported recurrence rates between 0 and 5%, but most have shorter follow-up times [26,27].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We describe a large series of patients with pHPT and their clinical evolution over time. Consistent with other series [17,26], we have obtained high cure (99%) and low recurrence (4.3%) rates. This study shows recurrences occurred with a median of 6.5 years after parathyroidectomy, whereas other studies have reported recurrence rates between 0 and 5%, but most have shorter follow-up times [26,27].…”
Section: Discussionsupporting
confidence: 92%
“…Classical manifestations of pHPT are related to kidney and skeletal damage, including nephrolithiasis, nephrocalcinosis, decreased renal function, low bone mineral density, bone cysts and brown tumors. In developed countries, however, the clinical presentation of pHPT has changed over the years and is now, in most cases, diagnosed in asymptomatic patients [15][16][17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…is might be related to older ages and PHPT clinical severity, as hypercalciuria-induced nephrogenic diabetes International Journal of Endocrinology insipidus often results in polyuria leading to volume depletion and a reduction in the glomerular filtration rate, which may lead to a further increase in calcium concentration [12]. Similarly, a retrospective study of 160 PHPT cases managed at a regional centre in the United Kingdom reported that higher peak calcium concentration was an independent predictor of acute kidney injury [13]. erefore, patients experiencing symptomatic hypercalcemia were older, with a reduced kidney function, experiencing higher comorbidity score and treated with a higher number of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Parathyroidectomy (PTX) is the only curative treatment for pHPT [1,2]. If successful, PTH and calcium levels are normalized.…”
Section: Introductionmentioning
confidence: 99%